STRATEGI PENGEMBANGAN USAHA KERIPIK PISANG DI KECAMATAN TEMBILAHAN KOTA KABUPATEN INDRAGIRI HILIR - Hendra Saputra; Sri Kartikowati; RM. Riadi RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Unfortunately the small business at chips bananas as one at community economic source in Indragiri Hilir, recently is not develop significantly, therefore it is needed to analysis a developmeat strategy to promate the business. In addition it should be examined proper development strategy to improve small businesses chips banana analyzed by one model matrix training .As for the purpose of this research is to know alternative strategy effective applied to develop small businesses chips bananas .The study is done at banana producers chips totaling 5 business unit. The research results show that small businesses chips bananas on the Tembilahan kota, Kecamatan Tembilahan Kota, Kabupaten Indragiri Hilir to the position of a V with concentration strategy is through horizontal or stability there is no change in income .Alternative strategy and can be applied to small chips mengembangakan bananas on the subdistrict tembilahan tembilahan the district capital indragiri hilir namely maintain banana chips as food the traditions of a society , the utilization of workers from the region around to increase production , pengoptimalan business management by adding capital, which has those produced to be maximum , introduce again that banana chips sentra as small food in the subdistrict tembilahan tembilahan the district capital indragiri downstream .Keywords: Development Strategy, Small Business